IMPLEMENTASI POLA PENDEKATAN DALAM MENGAJAR - elpina siburian; David Priyo Susilo; Eni Rombe (STT Kristus Alfa Omega, 2020)
Educators need to approach students to help them achieve their learning goals well. Based on observations, it is suspected that the pattern of approach taken by students is not optimal, so it becomes an obstacle to achieving the vision and mission of the Alfa Omega Semarang Theological Seminary. The researcher takes an objective measurement of the application of the approach pattern. The research method used is quantitative descriptive, which tests descriptive hypotheses. The result is that the Level of Implementation of the Approach Pattern in Teaching at the Alfa Omega Semarang Seminary Theology is in the medium category.